HUBUNGAN KEPATUHAN MINUM OBAT DENGAN PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI PROGRAM PROLANIS DIWILAYAH KERJA PUSKESMAS TAPA - Rahmalia Yacob; Rosmin Ilham; Fadli Syamsuddin (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Hypertension is one of the risk factors for cardiovascular disease that contributes to the highest mortality in Indonesia, so adherence to hypertension treatment is necessary. The purpose of this study is to determine the relationship between adherence to medication and a decrease in blood pressure in patients with hypertension in the prolanis program. The type of method is quantitative. The sample size was 60 respondents. The sampling technique was simple random sampling. Data collection used a questionnaire. The results of this study showed that most of the respondents who had adherence to taking medication were obedient 22 respondents (36.67%) and who had hypertension blood pressure level I 50 respondents (83.3%), quite obedient 20 respondents (33.33%), hypertension blood pressure level II 7 respondents (11.7%), disobedient 18 respondents (30.00%) and hypertension blood pressure level III 3 respondents (5.00%). The results of the chi-square statistical test (P-value = 0.003 <0.05) there is a significant relationship. Adherence to taking initial medication as an effort to lower blood pressure should be considered, and educate hypertensive patients about the schedule of taking medication and stopping medication after the doctor’s knowledge.